Can Asians Think of Peace? Essays on Managing Conflict in the Asian Century - Mahbubani, Kishore; Chandra, Varigonda Kesava; Tang, Kristen; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book explores the shifting dynamics of global power, highlighting Asia's resurgence. For centuries before the Western colonial era, China and India dominated the world economy. Now, Asia is reclaiming its historical prominence. China presents a formidable challenge to American power, while India is on track to become the world's third-largest economy by 2030. The 21st century is poised to be the Asian century, but will this rise be peaceful, or will it lead to catastrophic conflicts? Kishore Mahbubani, head and founder of the Asian Peace Programme (APP) at the National University of Singapore, offers a collection of 61 essays on peace in Asia, co-edited by Dr. Varigonda Kesava Chandra, and Kristen Tang. Written by scholars and practitioners from both Asia and the West between July 2020 and December 2024, these essays analyze potential flashpoints in Asia and propose pragmatic, implementable ideas for conflict management and peacebuilding. Topics include managing the US-China relationship, stabilizing India-Pakistan and China-India border conflicts, strengthening relations among Southeast Asian countries, and addressing global threats such as nuclear war and climate change. Mr. Mahbubani also provides a sharp introduction, contextualizing the conflict management and peacebuilding processes of the Asian 21st century.
Introduction -- Part 1: Asian ideas for peace and conflict amelioration -- Can Asians speak truth to power? -- Nuclear Deterrence 3.0 -- Asia, say no to NATO -- Freeze, talk and trade -- Technocratic deliberation and Asian peace -- America needs an economic peace strategy for Asia -- Where are the peacemakers?: -- Investing in peace for Asia -- Muslim Asia and the quest for peace -- Doubts about AUKUS -- Cyclone Mocha in conflict-ridden Myanmar is another warning to take climate change seriously -- Crisis management in Asia: A middle power imperative -- Rabindranath Tagore: A man for a new Asian future -- Asia should take the lead on global health -- Reconceptualizing Asia's security challenges: by Jean Dong, April 21, 2024 -- A new 'coalition of the unwilling' -- Asia's middle powers' activism a plus for regional stability -- Nuclear stability in the 21st century -- Part 2: Managing the US-China contest -- How China and US can avoid a clash in the South China Sea -- Beware of Munich -- The Anchorage meeting will buy America needed time -- Navigating troubled waters: Ideas for managing tensions in the Taiwan Strait -- It$1 (Bs dangerous salami slicing on the Taiwan issue -- US-China trade and investment cooperation amid great power rivalry -- Averting the grandest collision of all time -- China, America and the Saudi-Iranian normalization -- Coexistence: The only realist path to peace -- America can$1 (Bt stop China$1 (Bs rise -- Biden-Xi Summit: A positive step in managing complex US-China ties -- The US and China can lead the way on nuclear threat reduction -- Part 3: Conflict management in South Asia -- China and India: A new diplomacy -- Can South Asia put India-Pakistan hostilities behind to unite for greater good? -- An India-Pakistan ceasefire that can stick -- China and India: More new diplomacy -- Safer together: Why South and Southeast Asia must cooperate to prevent a new Cold War in Asia -- India-Pakistan: Peace by pieces -- India-China relations: Going beyond the military stalemate -- Restoring trust between China and India: A modest suggestion -- India can still be a bridge to the Global South -- Would you care for a 'package deal'? The future of a territorial swap on the disputed Sino-Indian boundary -- Why India-Pakistan relations need a new era of engagement -- Why have China and India come together? -- Part 4: Conflict management in Southeast and East Asia -- China and Japan: Will they ever reconcile? -- Islamist terrorism in Indonesia: Roots and responses -- The Biden era: Challenges and opportunities for Southeast Asia -- The oxygen of Asean -- An antidote against narrow nationalism? Why regional history matters -- Can Biden bring peace to Southeast Asia? -- Countering the threat of Islamist extremism in Southeast Asia -- HADR as a diplomatic tool in Southeast Asia-China relations amid changing security dynamics -- Can the Belt and Road Initiative bring peace to China and Asean -- Countering Moro youth extremism in the Philippines -- The EU and ASEAN: Partners to manage great power rivalry -- Caught in the middle? Not necessarily. Non-alignment could help Southeast Asian regional integration -- Managing expectations: Indonesia navigating its international roles -- US-China rivalry will be a stern test for Vietnam$1 (Bs diplomatic juggle -- Civilisational futures and the role of Southeast Asia -- The US, China, and the Philippines in between -- Singapore$1 (Bs role as a neutral interpreter of China to the West -- Securing China-US relations within the wider Asia-Pacific -- Southeast Asia, China, and the Belt and Read Initiative: still going strong? -- How Malaysia can boost Asean agency and centrality amid global challenges.s
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Peace; Asia -- Politics and government; International relations; Peace and Conflict Studies; Asian Politics; International Relations